Child Perpetrators and Victims: Criminal Policy Approaches to Sexual Violence in Indonesia through Restorative Justice - Redi Pirmansyah; Muh Zainul Arifin; M. Iqbal (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
Criminal law embodies the principle of ultimum remedium, which means that prosecution is considered a final measure in law enforcement. This principle does not seek to eliminate punishment for offenders but rather aims to protect society from crimes by using prosecution as a last resort. Offenses are not only committed by adults but also by minors. With the rapid advancement of information and telecommunication technology, sexually explicit content has become widely available through electronic media. As a result, many children mimic behaviors they have seen or heard about, particularly since they are often given access to electronic devices such as smartphones and computers with internet access. This ease of access sometimes occurs without sufficient parental supervision, exposing children to inappropriate content. Given this context, the author is motivated to conduct research titled Criminal Policy for Addressing Sexual Violence Committed by Minors Against Minors in Indonesia. This study aims to explore effective legal measures and policies to address and mitigate such incidents. The research employs a qualitative method grounded in the theory of sanctions and the theory of legal effectiveness. By utilizing a criminological approach, the study seeks to analyze crime patterns associated with sexual violence perpetrated by minors. This includes examining the socio-cultural factors that contribute to such behaviors and evaluating the current legal framework's effectiveness in addressing these issues. Through this research, the author hopes to shed light on the complexities of juvenile delinquency in the context of sexual violence and to propose informed policies that can better protect minors from both committing and becoming victims of such offenses. The findings are expected to contribute to the development of a more effective criminal justice system that balances punitive measures with rehabilitative approaches, ultimately aiming to create a safer and more just society for all.